2016
DOI: 10.1007/jhep09(2016)147
|View full text |Cite
|
Sign up to set email alerts
|

Neutrino mass, dark matter and anomalous magnetic moment of muon in a U 1 L μ − L τ $$ \mathrm{U}{(1)}_L{{}_{{}_{\mu}}}_{-}{{}_L}_{{}_{\tau }} $$ model

Abstract: The observation of neutrino masses, mixing and the existence of dark matter are amongst the most important signatures of physics beyond the Standard Model (SM). In this paper, we propose to extend the SM by a local L µ −L τ gauge symmetry, two additional complex scalars and three right-handed neutrinos. The L µ − L τ gauge symmetry is broken spontaneously when one of the scalars acquires a vacuum expectation value. The L µ − L τ gauge symmetry is known to be anomaly free and can explain the beyond SM measureme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 71 publications
(29 citation statements)
references
References 108 publications
1
28
0
Order By: Relevance
“…It has been noted, however, that gauging any difference between two lepton family numbers with an Abelian group leads to an anomaly free theory [468,469,469,470]. L µ − L τ is an explicit example which has been investigated in detail in [471][472][473][474][475][476][477][478][479][480][481]. The gauge group …”
Section: Existing Limitsmentioning
confidence: 99%
“…It has been noted, however, that gauging any difference between two lepton family numbers with an Abelian group leads to an anomaly free theory [468,469,469,470]. L µ − L τ is an explicit example which has been investigated in detail in [471][472][473][474][475][476][477][478][479][480][481]. The gauge group …”
Section: Existing Limitsmentioning
confidence: 99%
“…In our earlier work in ref. [32], we showed that our model can explain the nonzero neutrino masses and their intergenerational mixing angles. Also in that work, we considered the scalar field φ DM as a WIMP type dark matter candidate and checked its viability in various direct detection experiments.…”
Section: Jhep02(2017)123mentioning
confidence: 61%
“…The difference here with the previous work is that here we wish to produced the dark matter via the freeze-in mechanism instead of freeze-out, as in [32]. Our aim is to simultaneously explain the dark matter relic abundance as well as the muon (g − 2).…”
Section: Muon (G − 2) and Neutrino Massmentioning
confidence: 99%
See 2 more Smart Citations